Implementation of a Problem-Based Learning Model to Enhance Critical Thinking Skills in Leadership and Teamwork Learning at the Politeknik Pelayaran Sulawesi Utara - Muhammad Sapril Siregar; Semuel Palembangan; Haryadi Wijaya (PT. Alpha Trianguli Australis, 2026)
Managerial competence is the ability to manage resources through planning, organizing, implementing, and supervising activities to achieve organizational goals effectively and efficiently, especially in terms of the art of leading, controlling, commanding, coordinating, transacting, and serving which a manager must have in achieving goals organization. Therefore, this can only be obtained in leadership and teamwork courses. However, the current approach to teaching these skills often yields suboptimal results in terms of attitudes and learning outcomes. In response, we conducted a study aimed at elevating the quality of leadership and teamwork instruction through the implementation of a problem-based learning approach. This method prompts students to solve practical challenges simulating real-world workplace situations. This study used a qualitative approach with the Lesson Study method and Cluster Random Sampling with a study population of 24 participants consisting of 19 male and 5 female participants. The results showed that our research revealed 91.67% of participants achieved a score of at least 80, surpassing the targeted objective of 85%. Moreover, student engagement exceeded expectations, with an average activity rate of 86.67% against a target of 80%. In conclusion, the utilization of problem-based learning models can improve students' critical thinking skills in leadership and teamwork lessons.